Reproducibility and construct validity of the utrecht mixing ability Test to obtain masticatory performance outcome in patients with condylar mandibular fractures. (11th December 2019) - Weinberg, Florine M.; Vermaire, Jorine A.; Forouzanfar, Tymour; Rosenberg, Antoine J.W.P.; Speksnijder, Caroline M.
Abstract: Objective: This study assessed the test‐retest reproducibility of the Utrecht mixing ability test (MAT) and the construct validity of the MAT in relation to the Mandibular Function Impairment Questionnaire (MFIQ) in patients with mandibular condylar fractures. Material and methods: Twenty‐six patients treated for a mandibular condylar fracture participated in this clinimetric study; all patients performed the MAT twice. Simultaneously the MFIQ was conducted. Test‐retest reliability and construct validity were assessed using the intra‐class correlation coefficient (ICC) and Spearman correlation, respectively. Results: The ICC of the MAT was 0.906 (95% CI: 0.801‐0.957), which indicates an excellent reliability. A weak correlation of 0.386 ( P = .052) between the first MAT and the overall outcome of the MFIQ was found. A significant moderate correlation of 0.401 ( P = .042) was found between the retest of the MAT and the overall outcome of the MFIQ. One question on the MFIQ (about yawning) showed a moderate positive correlation of 0.569 ( P = .002) and 0.416 ( P = .034) for the MAT test and retest, respectively. Conclusion: The MAT is an easy test to use in follow‐up of patients. The test‐retest reliability of this test is excellent in condylar trauma patients. As the validity of the MAT and the MFIQ could not be confirmed, the MFIQ may be an addition to patient's feedback about the rehabilitation process of their mandibular functioning.